Missense mutations in CASK, coding for the calcium‐/calmodulin‐dependent serine protein kinase, interfere with neurexin binding and neurexin‐induced oligomerization. Issue 4 (4th November 2020) - Pan, Yingzhou Edward; Tibbe, Debora; Harms, Frederike Leonie; Reißner, Carsten; Becker, Kerstin; Dingmann, Bri; Mirzaa, Ghayda; Kattentidt‐Mouravieva, Anja A.; Shoukier, Moneef; Aggarwal, Shagun; Missler, Markus; Kutsche, Kerstin; et al.
Abstract: Mutations in the X‐linked gene coding for the calcium‐/calmodulin‐dependent serine protein kinase (CASK) are associated with severe neurological disorders ranging from intellectual disability (in males) to mental retardation and microcephaly with pontine and cerebellar hypoplasia. CASK is involved in transcription control, in the regulation of trafficking of the post‐synaptic NMDA and α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid receptors, and acts as a presynaptic scaffolding protein. For CASK missense mutations, it is mostly unclear which of CASK's molecular interactions and cellular functions are altered and contribute to patient phenotypes. We identified five CASK missense mutations in male patients affected by neurodevelopmental disorders. These and five previously reported mutations were systematically analysed with respect to interaction with CASK interaction partners by co‐expression and co‐immunoprecipitation. We show that one mutation in the L27 domain interferes with binding to synapse‐associated protein of 97 kDa. Two mutations in the guanylate kinase (GK) domain affect binding of CASK to the nuclear factors CASK‐interacting nucleosome assembly protein (CINAP) and T‐box, brain, 1 (Tbr1). A total of five mutations in GK as well as PSD‐95/discs large/ZO‐1 (PDZ) domains affect binding of CASK to the pre‐synaptic cell adhesion molecule Neurexin. Upon expression in neurons, we observe that binding to Neurexin is not required for pre‐synaptic localization of CASK. We show by bimolecular fluorescence complementation assay that Neurexin induces oligomerization of CASK, and that mutations in GK and PDZ domains interfere with the Neurexin‐induced oligomerization of CASK. Our data are supported by molecular modelling, where we observe that the cooperative activity of PDZ, SH3 and GK domains is required for Neurexin binding and oligomerization of CASK. Abstract : The pathogenic mechanism underlying several patient‐derived missense mutations of the MAGUK CASK remains unclear. MAGUKs have been shown to oligomerize when binding to their PDZ‐ligand through a conformational change in their PDZ, SH3 and GK domains. We demonstrate here that WT CASK also oligomerizes when bound to its PDZ‐ligand Neurexin, but that several of the 10 studied CASK mutant variants fail to bind to Neurexin and/or to oligomerize. This suggests that the loss of Neurexin‐induced oligomerization may be a key pathogenic mechanism underlying CASK missense mutations.